A Novel Method for Parkinson's Disease Diagnosis Utilizing Treatment Protocols. (2nd August 2022) - Al-Otaibi, Shaha; Ayouni, Sarra; Khan, Md Maruf Haque; Badr, Malek
Abstract : It makes no difference whether a person is male or female when it comes to neurodegenerative disorders; both sexes are equally susceptible to their devastating effects. Sometimes, it is unclear why a person in their life got a condition that is well-known in the world, such as Parkinson's disease. Other times, it is evident why the individual obtained the ailment (PD). In modern times, a variety of cutting-edge algorithms that are based on treatment protocols have been developed for the purpose of diagnosing Parkinson's disease. The approach that is presented in this article is the most current one; it was created using deep learning, and it can predict how severely Parkinson's disease would affect a patient. In order to diagnose this condition, it is necessary to conduct a comprehensive medical history, a history of any past treatments, physical exams, and certain blood tests and brain films. Because they are less time-consuming and costly, diagnoses are becoming an increasingly important part of medical practice. The diagnosis of Parkinson's disease by the physician is supported by the findings of the present research, which analyzed the voices of 253 participants. Preprocessing is done in order to get the most accurate results possible from the data. In order to carry out the technique of balancing, a methodical sampling approach was used to choose the data that would afterwards be evaluated. Using a feature selection approach that was determined by the magnitude of the label's influence, many data groups were created and organized. DT, SVM, and kNN are three methods that are used in classification algorithms and performance assessment criteria. The model was developed as a result of selecting the classification method and data group that had the greatest performance value. This decision led to the creation of the model. During the process of building the model, the SVM technique was used, and data comprising 45% of the original data set were utilized. The information was arranged in descending order of significance, beginning with the most pertinent. In addition to achieving exceptional outcomes in every other aspect of the project, the performance accuracy target was successfully met at 86 percent. As a consequence of this, it has been decided that the physician will be provided with medical decision support with the assistance of the data set obtained from the speech recordings of the individual who may have Parkinson's disease and the model that has been developed. This has led to the conclusion that medical decision support will be offered to the physician.